Early Mechanical and Microstructure Evolution Characteristics of Concrete in Steam Curing Condition - Liao, Shengrong; Xiao, Chunming; Cui, Yuhao; Xue, Yan (Geofluids, 2023)
In order to study the effect of steam curing on early mechanical properties of concrete, the strength, dynamic elastic modulus, and microstructure characteristics of concrete under different curing methods were tested. The results show that the early strength growth rate of steam curing concrete is obviously higher than that of standard curing. The strength development of concrete during steam curing can be divided into three stages. Stage I and stage II (0 h-30 h) are critical periods for concrete strength growth. The dynamic elastic modulus of steam-curing concrete is mainly formed in the early stage and shows a linear rapid growth characteristic. The growth rate of the dynamic elastic modulus of concrete under standard curing condition is relatively slow, but in the later curing period (30 h-48 h), the growth rate of dynamic elastic modulus of concrete is significantly higher than that of steam curing concrete. Steam curing can accelerate the production of cement hydration products which rapidly increases the early strength of concrete. Under the standard curing condition, the hydration product structure of concrete is more compact, which is conducive to the growth of dynamic elastic modulus in a later period. This study provides a theoretical reference for the application of steam curing in engineering, which is important to ensure the production efficiency and quality of concrete in engineering.